Beyond the check-up: how well-child exams, pediatric specialists, and provider recommendations can close HPV vaccine gaps for Chinese American Teens - Lin Zhu; Xinrui Li; Elaine Zhiqing Liu; Philip T. Siu; Shumenghui Zhai; Chun Pan; Nikki Cao; Grace X. Ma (Cancer Causes & Control, 2026)
Purpose This study aimed to identify provider- and practice-level factors influencing human papillomavirus (HPV) vaccine uptake among Chinese American (CA) adolescents. Despite increasing public health efforts, HPV vaccination rates in this population remain suboptimal, and knowledge on the link between provider/practice characteristics and vaccine uptake is limited. Methods We analyzed data from 1,272 CA adolescents (aged 13–17) using the National Immunization Survey-Teen (2015–2019) datasets. Key measures included HPV vaccine initiation and completion (based on proxy reporting and verification), accompanied by various multilevel factors: provider-level (recommendation, specialty), practice-level (facility type, vaccine acquisition, well-child exam), parent-level (mother’s education, marital status), and adolescent-level characteristics. Weighted descriptive statistics and stepwise multivariate logistic regression were used to examine associations. Results Overall, 71.22% of CA adolescents initiated at least one HPV vaccine dose, while 48.14% completed the regimen. Provider's recommendation (initiation OR = 21.50, completion OR = 8.12), having a pediatrician (initiation OR = 5.37, completion OR = 3.20), and receiving the 11–12-year-old well-child exams significantly predict both initiation and completion. Regional disparities were observed, with adolescents in the Northeast and West showing higher completion rates than those in the South. Unexpectedly, adolescents not enrolled in school and those with mothers who had less than 12 years of education or were unmarried showed higher completion rates. Conclusion Provider recommendations and pediatric care are crucial for improving HPV vaccination rates among CA adolescents. Addressing regional disparities and implementing targeted interventions, including enhanced provider training focused on culturally sensitive communication, are essential to dismantle systemic barriers and improve comprehensive vaccination coverage in this underserved population.

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)